Endomeriosis of Cesarean Section Why on Leet side? - Abbud, Ali Hl (AL-Kindy College Medical Journal, 2020)
Background: Endometriosis is defined as the presence or growth of ectopic endometrial tissue outside their usual site ( the uterus). It is a common condition in women. It may occur in the ovaries, fallopian tubes, vagina and rarely, endometriosis may occur in the abdomen and lungs. Endometriosis is common among women of reproductive age. It is either primary or secondary. The triad of diagnosis is a pain with menstruation, cesarean scar and a mass in the scar. Methods: A report a series of 65 patients in the period from 1st Jan 2013 to 31st Dec 2017. The study was performed in Al-Kindi Teaching Hospital and a private hospital. The mean age was 35 years (range 20-45).All patients were treated surgically i.e. excision of the tumor and old surgical scar in the lower abdomen. Result: mean age was 35 years (range 20-45). Thirty patients (46.15%) were housewives while 35(53.84%) were officers. The interesting finding is that 52 patients had the mass in the left side, 10 in the middle and only 3 in the right side of the scar respectively. Conclusion: Our study demonstrated a lateral asymmetry in the location of scar endometriosis i.e. mostly on the left side. The prevalence on left side of scar can be added to the triad of diagnosis mentioned above I.e. cyclical pain, cesarean scar and mass mostly in left side of the scar.